Permanent Deformation Characteristics of Flexible Pavement Under Palm Oil Freight Truck Loading - Setiawan, Dian M. (International Journal of Integrated Engineering, 2023)
Most of previous studies employed dynamic stability test and Hamburg wheel tracking test to investigate permanent deformation characteristics of asphalt concrete (AC) layer. However, the permanent deformation performance only focuses on the surface course and neglected the influence of middle layer and base course. The present study investigates the permanent deformation characteristics of four (4) different configurations of flexible pavement and analyzes the contribution of AC surface and AC base course to the total permanent deformation of AC layer as the response to various truck’s speed, hauling loads, and loading cycles. Finite element modeling was performed to evaluate critical locations below the tire tread of single unit two-axles truck with the greatest magnitude of permanent deformation and to determine the optimum configuration of flexible pavement by considering the linear viscoelastic behavior of two types of AC mixtures. It can be concluded that the largest permanent deformation is measured below the right edge of the outer tire. The contribution of AC surface course on the total permanent deformation due to the increase in truck’s speed is only about 14.81% to 16.39%, while the contribution of AC surface course on the total permanent deformation due to the increase in truck’s hauling loads as well as the increase in the number of passing trucks is only around 14.76% to 16.44%. On the other hand, the contribution of AC base course on the total permanent deformation due to the increase in truck’s speed from is reaching 83.61% to 85.19%, while the contribution of AC base course on the total permanent deformation due to the increase in truck’s hauling loads as well as the increase in the number of passing trucks is achieving 83.56% to 85.24%.